Using market data to understand corporate behaviour. (30th September 2020) - Hiscock, R
Abstract: Background: Tobacco companies sell tobacco in order to invest in the business and make profits for shareholders. One element in creating profitability is via data driven marketing. Such data are also useful for public health because an understanding of pricing and sales patterns can help with the development of effective tobacco control methods by understanding how the tobacco industry is making profits. Methods: Study 1) Public and commercial databases which provide free or paywalled access to market data were identified. Internet searches were conducted to understand more about their ownership, mission of the owners, funding and accessibility Study 2) University of Bath studies using such datasets to understand the tobacco industry were reviewed to synergise the ways in which corporate behaviour has undermined tobacco control policy. Results: The United Nations provides freely accessible national level statistics on imports and exports of raw tobacco and manufactured tobacco products. Limited survey data may be available on the last product smoked. Proprietary databases are expensive, may have usage restrictions and links to the tobacco industry but can provide a detailed picture of tobacco product sales and prices. Research on such databases has illustrated how the tobacco industry kept cheap tobacco available despite tobacco taxes, used tax rises to increase their own revenue and used a standardised packaging sell through period to keep branded packs on the market for longer. Conclusions: Governments should require the tobacco industry to provide market data in an easily publishable form Key messages: The most detailed data on the tobacco market is proprietary. Proprietary databases are expensive, may have usage restrictions and links to the tobacco industry. Understanding of pricing and sales patterns can help with evaluating the effectiveness of tobacco control policy.